Current pharmacotherapeutical options for the prevention of kidney transplant rejection - Schäfer, Sebastian Markus; Süsal, Caner; Sommerer, Claudia; Zeier, Martin; Morath, Christian (Expert opinion on pharmacotherapy, 2013)
Introduction: Advances in immunosuppression and medical care over the past years resulted in better short- and long-term graft survival following kidney transplantation. Novel potent immunosuppressive agents, combinations of proven substances and the steadily expanding knowledge on the pathophysiology of kidney transplant rejection allows the extension of donor and recipient criteria, including the usage of organs from ABO-incompatible and crossmatch-positive donors, to overcome the increasing problem of organ shortage. Areas covered: Immunosuppressive regimens for the prevention of kidney transplant rejections with a focus on regimens aiming at calcineurin inhibitor or steroid minimization, withdrawal or avoidance. Prevention of antibody-mediated rejections in standard-risk and sensitized recipients, as well as newly introduced immunosuppressive substances are covered. Expert opinion: Currently applied immunosuppressive regimens are associated with excellent short-term graft survival. However, the long-term outcomes of different regimens substantially differ with regard to potential side effects, graft function, rejection and sensitization rates. The adverse effects of effective immunosuppression must carefully be balanced against the benefit, e.g., prevention of the development of donor-specific human leukocyte antigen antibodies and chronic (antibody-mediated) rejection. The choice of the appropriate immunosuppressive regimen requires clinical experience and careful consideration of recipient and transplant characteristics to achieve an optimal long-term graft survival.